Identification of Market Demand for Omega-3 Eggs in Bogor Regency - Soesanto, Iman Rahayu Hidayati; Yani, Ahmad; Tanti, Ariyani (Jurnal Ilmu-Ilmu Peternakan, 2024)
The egg market is a crucial sector in the food industry. Eggs are not only an affordable and highly nutritious source of protein but also offer nutritional variations that can be tailored to consumer needs. Increasingly knowledgeable consumers and easily accessible information have opened new opportunities for the development of innovative food products that meet public health needs. One such product is omega-3-enriched eggs. This study aimed to identify the demand for omega-3 eggs in Bogor Regency. The survey method was used from August 22-23, 2023. The survey results indicate that most consumers are willing to purchase omega-3 eggs in large quantities, with 50% of respondents willing to pay Rp. 3000 per egg. These findings reflect high interest in increasing omega-3 fatty acid intake through accessible products. Furthermore, 37% of respondents often shop for eggs at supermarkets, indicating a significant opportunity for product placement in major retail stores. Practical packaging with plastic mica was also preferred by 70% of respondents due to its practicality and efficiency. Thus, omega-3 eggs can be developed in Bogor Regency because they meet market needs and offer promising business opportunities.